2016
DOI: 10.1038/srep36446
|View full text |Cite
|
Sign up to set email alerts
|

The Mutation of Glu at Amino Acid 3838 of AtMDN1 Provokes Pleiotropic Developmental Phenotypes in Arabidopsis

Abstract: MDN1/Rea1, as an AAA-type ATPase, is predicted to be the largest protein involved in pre-ribosome maturation in most organisms. However, its function in plant growth and development is poorly understood. Here, we characterized a novel Arabidopsis mutant, dwarf & short root (dsr) 1, which shows pleiotropic developmental phenotypes, such as slow germination, short root, dwarf shoot, and reduced seed set under normal growth conditions. Using positional cloning, we revealed that the AtMDN1 function is impaired by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 24 publications
4
26
0
Order By: Relevance
“…1A). The phenotype of the mdn1-1 silique has been presented in our previous study (Li et al, 2016b). As described by Chantha et al (2010), a heterozygous T-DNA insertion mutant allele of MDN1 (Salk_057010), which we call "mdn1-2/+" in this study, also exhibits the phenotype of reduced seed set per silique.…”
Section: Mdn1 Is Essential For Embryo Developmentsupporting
confidence: 51%
See 2 more Smart Citations
“…1A). The phenotype of the mdn1-1 silique has been presented in our previous study (Li et al, 2016b). As described by Chantha et al (2010), a heterozygous T-DNA insertion mutant allele of MDN1 (Salk_057010), which we call "mdn1-2/+" in this study, also exhibits the phenotype of reduced seed set per silique.…”
Section: Mdn1 Is Essential For Embryo Developmentsupporting
confidence: 51%
“…In maize (Zea mays), the reduced function of RIBOSOME EXPORT ASSO-CIATED1 (the counterpart of MDN1) results in delayed embryo, endosperm, and seedling development (Qi et al, 2016). Furthermore, we previously characterized an Arabidopsis mutant, dwarf and short root (dsr1; renamed mdn1-1 in this study), which contained a missense mutation in MDN1 and displayed phenotypes such as a short root and low seed set under normal growth conditions (Li et al, 2016b). These results imply that MDN1 is also vital for normal plant growth and development.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In Arabidopsis, MCM2 is involved in DNA replication and is important for root meristem maintenance (Ni et al 2009), and mutations in a DNA helicase/nuclease result in very short roots (Jia et al 2016). Further, mutation of AtMDN1, an AAA-ATPase that is a component of the pre-60S ribosome, results in several developmental defects including a shorter root (Li et al 2016). Histone modifications have also been shown to be critical for proper root growth and development (reviewed in Takatsuka and Umeda 2015).…”
Section: Resultsmentioning
confidence: 99%
“…No plant homologs of yeast Rsa4 have thus far been reported. However, characterization of the dwarf and short root1 (dsr1) mutant revealed that DSR1 is the Arabidopsishomolog of the yeast Rea1 and human MDN1 proteins (Li et al, 2016). Mutating a key amino acid position in ArabidopsisMDN1 (Glu to Lys at position 3838) induces pleiotropic developmental phenotypes, including slow germination, short roots, dwarf shoots, and reduced seed set (Li et al, 2016).…”
Section: Maturation Of Pre-60s Particlesmentioning
confidence: 99%